Hypersonic interference aerothermodynamics - Estruch-Samper, David (Cranfield University, 2009)
When a vehicle travels at hypersonic speeds during launch, cruise or atmospheric re-entry it is subject to extremely high surface flow temperatures. As well as on the vehicle forebody, extreme heating can take place close to surface protuberances which are almost impossible to avoid in a real flight vehicle. These disturbances interfere with the freestream flow and result in complex viscous interactions which induce a local heat flux augmentation that can become detrimental to the integrity of the vehicle. A greater understanding of these flow phenomena is required. This thesis develops the understanding of the behaviour of the flow around surface protuberances in hypersonic vehicles and presents an engineering approach to predict the location and magnitude of the highest heat transfer rates in their vicinity. To this end, an experimental investigation was performed in a gun tunnel at freestream Mach numbers of 8.2 and 12.3 and Reynolds numbers ranging from Reoo/m=3.35xl0 ⁶ to Reꚙ /m=9.35xl0 ⁶. The effects of protuberance geometry, boundary layer state, freestream Reynolds number and freestream Mach number were assessed. Further understanding of the flowfield was obtained through oil-dot visualisations and highspeed schlieren videos taken at frame rates of up to 50 kHz. Results show the local interference interaction is strongly three-dimensional and is dominated by the incipient separation angle induced by the protuberance. In subcritical interactions - in which the incoming boundary layer remains unseparated upstream of the protuberance - the highest heating occurs adjacent to the device. In supercritical interactions - in which the incoming boundary layer is fully separated ahead of the protuberance - the highest heating generally occurs on the surface just upstream of it. An exception is for low-deflection protuberances under low-Reynolds freestream flow conditions in which case the heat flux to the side is greater.